Seed Elaiosome Mediates Dispersal by Ants and Impacts Germination in Ricinus communis - Sasidharan, Rohit; Venkatesan, Radhika (Frontiers in Ecology and Evolution, 2019)
Myrmecochory is ant-mediated secondary dispersal of seeds that depends on the presence of a lipid-rich seed appendage known as ‘elaiosome’. Attractive cues of elaiosome that drive such an interaction and benefits to the plant are not clearly understood. Here, using Ricinus communis, we establish reward compositions and determine the benefits of myrmecochory to the plant. We also compare elaiosome compositions across ecotypes. Our results show that the elaiosome is essential for seed displacement and olfactory cues are important attractive cues. Nonanal and 2-decenal were found to be the major attractive volatiles in the castor elaiosome. Different ant species showed different behavior towards elaiosome-bearing seeds. Among them, Pheidole grayi was efficient in dispersal but did not disperse all seed ecotypes tested. Major differences in fatty acid levels were observed between ecotypes. To determine the benefits of myrmecochory, germination rates before and after removal of elaiosome were studied. Seed germination improved upon elaiosome removal and aqueous elaiosome extract inhibited germination indicating water-soluble inhibitory factors. Further, ant nest sites were richer in nitrogen than control sites, revealing a clear benefit of seed displacement. In summary, we demonstrate the ecological significance of the seed elaiosomes in the absence of nutritive rewards for seed dispersers.